Artistic Creation and Corporeity as Tools of Social Cohesion and Interculturality - García von Hoegen, Magda Angélica (2019)
The purpose of this article is to go deeper into artistic creation as a human right and as a means of encounter and interaction in fragmented societies. It also analyzes the body as a place of epistemic construction. The study was conducted between 2013 and 2016 in the municipalities of Tactic and San Cristóbal, Alta Verapaz, Guatemala, and complementary research took place in the regions of Coto, Abrojo de Moctezuma, and Rey Curré in Costa Rica. The methodology used in this study was participatory research with young people through a creative-artistic action in four areas: dance, theater, poetry, and music. The information collected during this stage was deepened in focus groups, life stories, and in-depth interviews. The findings demonstrate that it is possible to strengthen the bonds of solidarity, cohesion, and reconstruction of the communities from the creation of artistic works based on the complex realities lived by youth, and also to develop self-esteem, deepen aspects of individual and collective identity, generate actions of social transformation, build historical memory, and foster alliances between different sections of the community.